Examining multidimensional internationalization and institutional development in a global south university: Evidence from a Philippine public higher education institution - GAS-IB, PINKY LARCELLE; WACAS, ETHEL JOVY; OCAY, ABIGAIL; MARIANI, MATHEW JUN; Nguyen, Lan Thi Kim (Journal of Interdisciplinary Studies in Education, 2026)
Internationalization has become a strategic priority in higher education institutions seeking to strengthen global engagement and institutional capacity aligned with Sustainable Development Goal 4. This study examined how multidimensional internationalization practices relate to institutional development and perceived internationalization performance in a Philippine public university using an explanatory sequential mixed-methods design involving 146 survey respondents and 15 interview participants. Structural equation modeling revealed significant associations among internationalization in instruction, research collaboration, extension partnerships, gender inclusivity, and institutional development, which strongly predicted internationalization performance. Qualitative findings highlighted institutional constraints, inclusivity concerns, and resource-sensitive implementation strategies. The study emphasizes the importance of inclusive, context-responsive, and institutionally supported internationalization approaches in Global South public universities.